Operaciones con resultado ( Cubo de un binomio)
( 5a + 2b)^3 = (5a)^3 + 3(5a)^2(2b) + 3(5a)(2b)^2 + (2b)^3
................ = 125a^3 + 150a^2b + 60ab^2 + 8b^3
( 2x ^2 - y^3)^3 = (2x^2)^3 - 3(2x^2)^2(y^3) + 3(2x^2)(y^3)^2 - (y^3)^3
......... = 8x^6 - 12x^4y^3 + 6x^2y^6 - y^9
( 3m + 1/3k)^3 = (3m)^3 + 3(3m)^2(1/3k) + 3(3m)(1/3k)^2 + (1/3k)^3
.......... = 37m^3 + 9m^2k + mk^2 + 1/27k^3
( ∛b - ∛d)^3 = (∛b)^3 - 3(∛b)^2(∛d) + 3(∛b)(∛d)^2 - (∛d)^3
.......... = b - 3 ∛(b^2 d) + 3∛(bd^2) - d
( x + 1/x)^3 = x^3 + 3 x^2(1/x) + 3 x (1/x)^2 + (1/x)^3
................ = x^3 + 3 x + 3/x + 1/x^3
(a±b)3 =a3±3·a2·b+3·a·b2±b3
(x+3)3 =x3+3·x2·3+3·x·32+33=
...........=x3+9x2+27x+27
(2x−3)3=(2x)3−3·(2x)2·3+3·2x·32−33=
........= 8x3−36x2+54x−27
No hay comentarios:
Publicar un comentario